Neurotuberculosis as a complication of miliary tuberculosis in a vaccinated infant: Case report (Research, Society and Development, 2024)
Tuberculosis (TB) is a disease of public importance, representing a frequent cause of death in all age groups. Caused by Mycobacterium tuberculosis, affecting humans pulmonary or extrapulmonary, as well as by hematogenous dissemination affecting multiple organs, receiving the name Miliary Tuberculosis. It gets its name from the radiological pattern, and in many cases is fatal if not diagnosed and treated properly. The goal is to report a case of miliary tuberculosis in an infant and with a positive contact in the pediatrics service of the Hospital Universitário Maria Aparecida Pedrossian (HUMAP). This is an observational, descriptive and reflective case report. Data were obtained through electronic medical records, after approval by the Research Ethics Committee. Patient 7 months old referred due to radiographic findings suggestive of miliary TB. During hospitalization, mother and patient received a confirmed diagnosis of TB. During treatment, the patient developed neurological impairment and was diagnosed with neurotuberculosis, developing permanent neurological sequelae. Furthermore, he was able to receive medical discharge following outpatient follow-up. It is concluded that TB is a disease of public importance, and its prevalence in the pediatric population is directly proportional to the efficiency of health actions.